2014
DOI: 10.1007/s11999-014-3523-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Bone Adaptation Adjacent to Percutaneous Osseointegrated Prostheses in a Sheep Model

Abstract: Background Percutaneous osseointegrated prostheses (POPs) are being investigated as an alternative to conventional socket suspension and require a radiographic followup in translational studies to confirm that design objectives are being met. Questions/purposes In this 12-month animal study, we determined (1) radiographic signs of osseointegration and (2) radiographic signs of periprosthetic bone hypertrophy and resorption (adaptation) and (3) confirmed them with the histologic evidence of host bone osseointeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Geometrical fit between the implant and the bone appears to be crucial for a successful outcome as observed by loosening and failure of undersized implants, 5 , 8 or fracture at the insertion of oversized implants. 44 Bone ingrowth is dependent on the implant material, the implant design, and the geometrical fit in the bone. 9 In all of the studied implant systems except the ILP, the bulk material of the implant is the titanium alloy Ti6Al4 V. In the ILP, a cobalt-chrome-molybdenum alloy is used instead.…”
Section: Resultsmentioning
confidence: 99%
“…Geometrical fit between the implant and the bone appears to be crucial for a successful outcome as observed by loosening and failure of undersized implants, 5 , 8 or fracture at the insertion of oversized implants. 44 Bone ingrowth is dependent on the implant material, the implant design, and the geometrical fit in the bone. 9 In all of the studied implant systems except the ILP, the bulk material of the implant is the titanium alloy Ti6Al4 V. In the ILP, a cobalt-chrome-molybdenum alloy is used instead.…”
Section: Resultsmentioning
confidence: 99%
“…Osseointegrated implant research has been conducted in animal models looking at the bone [6][7][8][9][10] and soft tissue response [11][12][13]. Post-operative outcomes have been published for transhumeral OI implanted patients implanted abroad [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to circumvent these outcomes, an end-loading endoprosthesis was designed. Research conducted jointly at the VA Salt Lake City Health Care System and at the University of Utah Orthopaedic Center has shown that a porous commercially pure titanium coating provided a stable integration of bone with a titanium-alloy endoprosthesis [1216]. The design consisted of a line-to-line endoprosthesis that fit the surgically prepared medullary canal of the transmetaphyseal-amputated, fused 3–4 metacarpal of the sheep forelimb [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted jointly at the VA Salt Lake City Health Care System and at the University of Utah Orthopaedic Center has shown that a porous commercially pure titanium coating provided a stable integration of bone with a titanium-alloy endoprosthesis [1216]. The design consisted of a line-to-line endoprosthesis that fit the surgically prepared medullary canal of the transmetaphyseal-amputated, fused 3–4 metacarpal of the sheep forelimb [12, 16]. Sheep were chosen for the investigation [12, 16], because they provided a translational large animal model with both body weight and bone remodeling rate comparable to those of an adult human [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation